Coping Strategies for Parents with Autistic Children: a Review from Islamic Psychology - Bantali, Ampun; Athar, Gadis Arniyati (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to identify the sources of stress and coping strategies employed by parents and to provide a review from the perspective of Islamic psychology. The research was conducted using a phenomenological approach in Binjai, North Sumatra. The informants comprised five main participant, namely parents of autistic children who met the predetermined criteria, and three supporting informants. Information was gathered using in-depth interviews. The main findings indicated that the sources of parental stress are caused by the parents' lack of knowledge about autism, the difficulty of acceptance from the social environment and extended family, especially for single male autistic children from the Batak/Karo ethnic group who are expected to be the heirs of the clan, the high costs of care and education for autistic children, and uncertainty about the future. Parents who employ all four stress coping strategies show better stress control, which helps their autistic children achieve better development. From the perspective of Islamic psychology, these four strategies are fundamental attitudes of a Muslim in facing problems. This study also found that social and economic support have a greater influence than parental education on stress management. There is currently no community for parents of autistic children in Binjai, and autistic children have talents that can hold economic value. Therefore, it is necessary to form a parent community and an economic empowerment program based on the talents of autistic children.